Metabolic studies of a fructose-intolerant yeast by in vivo 31P-nuclear magnetic resonance spectroscopy. - Doyle, T; Spickett, C; Donaldson, I; Ratcliffe, R (1993)
The metabolic effects of the administration of fructose to a yeast expressing the cDNA for rat liver ketohexokinase have been investigated by 31P-nuclear magnetic resonance spectroscopy. Cessation of growth suffered by the yeast on exposure to 5 and 25 mM-fructose was accompanied by a large accumulation of fructose 1-phosphate at the expense of cytoplasmic orthophosphate and nucleoside triphosphate. Shifts in resonances were consistent with a drop in cytoplasmic pH. Arresting growth with 1 mM-fructose, however, did not result in these changes, although a large accumulation of fructose 1-phosphate occurred which may have been supported by the mobilization of polyphosphates.